2019
DOI: 10.1186/s12861-019-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

A dose-dependent response to MEK inhibition determines hypoblast fate in bovine embryos

Abstract: Background The segregation of the hypoblast and the emergence of the pluripotent epiblast mark the final stages of blastocyst formation in mammalian embryos. In bovine embryos the formation of the hypoblast has been partially studied, and evidence shows that MEK signalling plays a limited role in the segregation of this lineage. Here we explored the role of different signalling pathways during lineage segregation in the bovine embryo using immunofluorescence analysis of NANOG and SOX17 as readouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 37 publications
5
53
4
2
Order By: Relevance
“…In contrast to PHD medium, N2B27 allows both complete hypoblast migration and epiblast development. Hypoblast proliferation, previously reported in the PHD system based on conventional histology and electron microscopy ( Brandao et al 2004 ), was confirmed by immunostaining for SOX17, an hypoblast marker ( Canizo et al 2019 ). However, irrespective of the substrate used, hypoblast cells did not cover the entire surface of the embryos developed in PHD medium, while all embryos developed in N2B27 medium showed complete hypoblast migration.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast to PHD medium, N2B27 allows both complete hypoblast migration and epiblast development. Hypoblast proliferation, previously reported in the PHD system based on conventional histology and electron microscopy ( Brandao et al 2004 ), was confirmed by immunostaining for SOX17, an hypoblast marker ( Canizo et al 2019 ). However, irrespective of the substrate used, hypoblast cells did not cover the entire surface of the embryos developed in PHD medium, while all embryos developed in N2B27 medium showed complete hypoblast migration.…”
Section: Discussionsupporting
confidence: 63%
“…Later, during the second lineage segregation, ERK inhibition abrogates hypoblast formation in mouse and rabbit embryos ( Nichols et al., 2009 ; Piliszek et al., 2017 ). In contrast, in human ( Kuijk et al., 2012 ; Roode et al., 2012 ), pig ( Rodriguez et al., 2012 ), and cattle ( Canizo et al., 2019 ; Kuijk et al., 2012 ), ERK inhibition only partially blocks the hypoblast program, suggesting that additional signals regulate segregation of this lineage in non-murine embryos.…”
Section: Peri-implantation Development In Mammalian Embryos With Bilaminar Discsmentioning
confidence: 99%
“…Functional complementarity between human and other large mammalian embryos also find parallels in the signaling principles governing lineage decisions in the early embryo. During the first lineage decision segregating the TE and ICM, for example, inhibition of ERK signaling from the morula stage in pig and cattle promotes expansion of the TE in blastocysts (Canizo et al, 2019;Rodriguez et al, 2012). Although information on how human embryos respond to this treatment is lacking, experiments using naive human ESCs show that they readily differentiate into TE upon ERK inhibition alone (Guo et al, 2020).…”
Section: Reviewmentioning
confidence: 99%
“…On the contrary, expression of NANOG fails in OCT4-deficient bovine blastocysts, while the early presumptive hypoblast marker GATA6 is still present. Yet, it remains unclear if OCT4 has a role in the second lineage differentiation in bovine embryos, as GATA6 does not exclusively mark cells committed to the hypoblast, but also cells in the TE [9,10].…”
Section: Introductionmentioning
confidence: 99%